Mobilität und Zeugenschaft: Unabhängige Dokumentarfilmpraktiken und der Kaschmirkonflikt - Kramer, Max (transcript, 2018)
Is it possible to make independent documentaries in conflict regions? Max Kramer illuminates the relevance of mobility and witnessing in contemporary documentary practices.